Seismic Observations in the Taipei Metropolitan Area Using the Downhole Network - Win-Gee Huang; Bor-Shouh Huang; Jeen-Hwa Wang; Kou-Cheng Chen; Kuo-Liang Wen; Shuhjong Tsao; Yu-Chung Hsieh; Chi-Hsuan Chen (Terrestrial, Atmospheric and Oceanic Sciences, 2010)
Underlain by soft soils, the Taipei Metropolitan Area (TMA) experienced major damage due to ground-motion amplification during the Hualien earthquake of 1986, the Chi-Chi earthquake of 1999, the Hualien earthquake of 2002 and the Taitung earthquake of 2003. To study how a local site can substantially change the characteristics of seismic waves as they pass through soft deposits below the free surface, two complementary downhole seismic arrays have been operated in the TMA, since 1991 and 2008. The accelerometer downhole array is composed of eight boreholes at depths in excess of 300 meters. The downhole array velocity sensor collocated with accelerometer composed of four boreholes at depths up to 90 meters. The integrated seismic network monitors potential earthquakes originating from faults in and around the TMA and provides wide-dynamic range measurement of data ranging in amplitude from seismic background noise levels to damage levels as a result of shaking. The data sets can be used to address on the response of soft-soil deposits to ground motions. One of the major considerations is the nonlinear response of soft soil deposits at different levels of excitation. The collocated acceloerometer and velocity sensors at boreholes give the necessary data for studies of non-linearity to be acquired. Such measurements in anticipation of future large, damaging earthquakes will be of special importance for the mitigation of earthquake losses.